2010
DOI: 10.1161/circulationaha.109.895458
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective Study of Placental Angiogenic Factors and Maternal Vascular Function Before and After Preeclampsia and Gestational Hypertension

Abstract: Background-Preeclampsia is a life-threatening pregnancy syndrome of uncertain origin. To elucidate the pathogenesis, we evaluated the temporal relationships between changes in vascular function and circulating biomarkers of angiogenic activity before and after the onset of preeclampsia and gestational hypertension. Methods and Results-Maternal mean arterial pressure, uterine artery pulsatility index, brachial artery flow-mediated dilatation, and serum concentrations of placental growth factor (PlGF), soluble f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
236
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(276 citation statements)
references
References 48 publications
(50 reference statements)
24
236
2
8
Order By: Relevance
“…In agreement with the cytokine, chemokine and pentraxin-3 data, this might indicate less intense inflammatory response in multiparous compared to nulliparous women, possibly related to immune regulatory effects of previous pregnancies. In accordance with several previous studies, we found a highly significant increase in the anti-angiogenic factor sFlt-1 and decrease of the pro-angiogenic factor PlGF in women with preeclampsia, both for nulliparous and multiparous women (5,37,38). However, no obvious correlation was found between these factors and markers for coagulation and inflammation, suggesting that these pathogenic mechanisms are in part independent or separated in time.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with the cytokine, chemokine and pentraxin-3 data, this might indicate less intense inflammatory response in multiparous compared to nulliparous women, possibly related to immune regulatory effects of previous pregnancies. In accordance with several previous studies, we found a highly significant increase in the anti-angiogenic factor sFlt-1 and decrease of the pro-angiogenic factor PlGF in women with preeclampsia, both for nulliparous and multiparous women (5,37,38). However, no obvious correlation was found between these factors and markers for coagulation and inflammation, suggesting that these pathogenic mechanisms are in part independent or separated in time.…”
Section: Discussionsupporting
confidence: 91%
“…However in literature PLGF has been ascertained to be lower in early PE versus controls. 5,9 Being a prospective study, our study showed association between lower PLGF levels in first trimester to development of preeclampsia and gestational hypertension.…”
Section: Performance Of Plgf (Biochemical Marker)mentioning
confidence: 56%
“…En el caso de la PE, este proceso de variación de los niveles de sFlt-1 y PIGF parecen ocurrir mucho antes, lo que conllevaría a la disfunción endotelial (6,8). La PE de inicio temprano también se conoce como PE placentaria porque su etiología se asocia con una placentación anormal bajo condiciones hipóxicas con niveles elevados de sFlt-1 y bajos niveles de PIGF, y se cree que la sobre expresión de la sEng y sFlt-1 inhibe el remodelamiento de la arteria espiral en la interfase placentaria, es decir este proceso se da desde el inicio del embarazo (13,14). En contraste la PE de inicio tardío, o PE materna, no se asocian a una placentación anormal, sino que se considera una respuesta descompensada al estrés oxidativo generado por una disfunción endotelial placentaria que hace a la mujer susceptible al daño microvascular y alteración en el desarrollo de estructuras cardiovasculares fetales (6,15).…”
Section: Discussionunclassified
“…Auger y cols reportaron una asociación significativa entre la PE de inicio temprano y el desarrollo de CC de tipo crítico con una razón de prevalencia de 2,78 (IC95% 1,71-4,50), una diferencia de prevalencia de 249,6 en 100.000 y un RR ajustado de 2,8 (IC95% 1,8-4,4). Por otro lado, Brodwall y cols reportaron que la PE de inicio temprano tanto leve como severa estuvieron asociados con un incremento de riesgo de CC con un RR de 15,5 (IC95% 7,9-30,4) y un RR ajustado de 13,5 (IC95% 6,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]8), especialmente con la doble salida del ventrículo derecho (double outlet right ventricle, DORV), síndrome de corazón derecho hipoplásico (hypoplastic right heart síndro-me, HRHS), coartación de la aorta y con defecto del tabique auriculoventricular (atrioventricular septal defect, AVSD); esta última, presente en más del 25% de los casos de PE de inicio temprano severo. Solo se encontró un incremento de riesgo de CC en el grupo de PE severa tardía con un RR de 1,7 (IC95% 1,2-2,4).…”
Section: Discussionunclassified